Advancement in Cancer Stem Cell Biology and Precision Medicine—Review Article Head and Neck Cancer Stem Cell Plasticity and the Tumor Microenvironment - Heft Neal, Molly E.; Brenner, J. Chad; Prince, Mark E. P.; Chinn, Steven B. (Frontiers in Cell and Developmental Biology, 2022)
Head and Neck cancer survival has continued to remain around 50% despite treatment advances. It is thought that cancer stem cells play a key role in promoting tumor heterogeneity, treatment resistance, metastasis, and recurrence in solid malignancies including head and neck cancer. Initial studies identified cancer stem cell markers including CD44 and ALDH in head and neck malignancies and found that these cells show aggressive features in both in vitro and in vivo studies. Recent evidence has now revealed a key role of the tumor microenvironment in maintaining a cancer stem cell niche and promoting cancer stem cell plasticity. There is an increasing focus on identifying and targeting the crosstalk between cancer stem cells and surrounding cells within the tumor microenvironment (TME) as new therapeutic potential, however understanding how CSC maintain a stem-like state is critical to understanding how to therapeutically alter their function. Here we review the current evidence for cancer stem cell plasticity and discuss how interactions with the TME promote the cancer stem cell niche, increase tumor heterogeneity, and play a role in treatment resistance.